Mediation Role of External Locus of Control on the Influence of Financial Attitude and Financial Knowledge on Financial Management Behavior - Mentari Clara Dewanti; Daisy Martina Rosyanti; Fani Khoirotunnisa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine how the external locus of control mediates the influence of financial attitudes and financial knowledge on financial management behavior. Data was collected using a questionnaire distributed online to students majoring in management belonging to class Z UPN "Veteran" East Java. In this study, the SEM method used is Structural Equation Modeling based on Partial Least Square. Based on the results of data analysis that has been carried out, it was found that financial attitudes and external locus of control have a positive effect on financial management behavior. However, the difference in results shown by students' financial knowledge has no impact on their behavior in managing finances. The external locus of the control variable has a significant influence in mediating the effect of financial expertise on financial management behavior. An individual with sound financial knowledge can create a high external locus of control from individuals that impact awareness in increasing financial management behavior. Further research is directed to develop a research model with more diverse objects to gain a more comprehensive understanding, for example, Generation Z in other cities.